Platelet-Rich Plasma Versus Microfragmented Adipose Tissue for Knee Osteoarthritis: A Randomized Controlled Trial. Issue 9 (16th September 2022) - Baria, Michael; Pedroza, Angela; Kaeding, Christopher; Durgam, Sushmitha; Duerr, Robert; Flanigan, David; Borchers, James; Magnussen, Robert
Background: Platelet-rich plasma (PRP) has been established as safe and effective for knee osteoarthritis (OA). Another orthobiologic therapy, microfragmented adipose tissue (MFAT), has gained attention because of its heterogeneous cell population (including mesenchymal stem cells). However, prospective comparative data on MFAT are lacking. Because of the safety, efficacy, and simplicity of PRP, new therapeutics such as MFAT should be compared directly with PRP. Purpose: To compare patient-reported outcomes of a single injection of PRP versus MFAT for knee OA. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: A total of 58 patients with symptomatic knee OA (Kellgren-Lawrence grades 1-4) were randomized to receive a single injection of either leukocyte-rich PRP or MFAT under ultrasound guidance. PRP was created by processing 156 mL of whole blood. MFAT was created by harvesting 30 mL of adipose tissue via standard lipoaspiration. Scores for the Knee injury and Osteoarthritis Outcome Score (KOOS) subscales and visual analog scale for pain with Activities of Daily Living (VAS-ADL) were recorded at baseline and at 1, 3, and 6 months after the injection. The primary outcome was the KOOS–Pain subscore at 6 months after the injection. Results: The PRP group (n = 30) had a mean volume of 5.12 ± 1.12 mL injected. This consisted of a mean platelet count of 2673.72 ± 1139.04 × 10 3 /µL and mean leukocyte count of 25.36 ± 13.27 × 10 3 /µL (67.81% lymphocytes, 18.66% monocytes, and 12.33% neutrophils). The MFAT group (n = 28) had a mean volume of 7.92 ± 3.87 mL injected. The mean total nucleated cell count was 3.56 ± 4.62 million/mL. In both groups, KOOS subscale and VAS-ADL scores improved from baseline, and there was no significant difference between the PRP and MFAT groups in the final KOOS–Pain subscore (80.38 ± 16.07 vs 81.61 ± 16.37, respectively; P = .67) or any other outcome score. Conclusion: A single injection of either PRP or MFAT resulted in a clinically meaningful improvement for patients with knee OA at 6 months, with no difference between treatment groups. Registration: NCT04351087 (ClinicalTrials.gov identifier).